The complementary therapist's guide to red flags and referrals - Stephenson, Clare (London: Churchill Livingstone Elsevier, 2013)
Suitable for all complementary medicine, massage therapy and manual therapy practitioners and students alerting them to 'red flag' symptoms, this title offers guidance on how best to respond to those symptoms and signs of disease which can be readily discerned through routine history taking and basic examination of the body. --
Contents note continued: Choice of method of communication -- The structure and content of the communication -- Sample letter for referring patients to medical practitioners -- ch. 6 Red flags and referrals: ethical points -- The importance of clear records -- If in doubt, seek advice -- Maintaining confidentiality.
Includes bibliographical references and index.
Keywords: Alternative medicine -- Handbooks, manuals, etc; Diagnosis; Diseases -- Handbooks, manuals, etc; Medical care; Alternative medicine; Fritz, Sandy; Morris, William; Hopwood, Val; Complementary Therapies -- Handbooks; Referral and Consultation -- Handbooks; Signs and Symptoms -- Handbooks